Fracture of bone tissue: the 'hows' and the 'whys' - Gupta, Himadri; Zioupos, Peter (Elsevier, 2008)
The mechanical performance of bone is of paramount importance for the quality of life we experience. The structural integrity of bone, its hierarchical structure, organisation and its physicochemical constitution, all influence its ability to withstand loads, such as those seen occasionally in everyday life loading scenarios, which are either above the norm, prolonged, or repetitive. The present review explores three interconnected areas of research where significant progress has been made lately: (i) The recorded mechanical behaviour of bone and the way it fails; (ii) the inner architecture, organisational, hierarchical structure of bone tissue; and (iii) the bone properties at the micro/nanostructural and biophysical level. Exercising a line of thought along a structure/function based argument we advance from ‘how’ bone fractures to ‘why’ it fractures, and we seek to obtain a fresh insight in this field.
Keywords: Hierarchy; Mechanisms; Bone; Fracture; Properties; Structure